2015
DOI: 10.1002/pbc.25411
|View full text |Cite
|
Sign up to set email alerts
|

Survivors of standard risk acute lymphoblastic leukemia do not have increased risk for overweight and obesity compared to non‐cancer peers: A report from the Children's Oncology Group

Abstract: Background We sought to determine whether survivors of standard risk ALL (SR-ALL) treated without cranial radiation have increased risk for obesity by assessing changes in body mass index (BMI) during and after treatment; identifying contributing patient and treatment factors; comparing rates of overweight/obese to national health data. Procedure Eligibility for this retrospective cohort study included 1) previous enrollment on legacy therapy trials CCG1922 or CCG1952; 2) continuous first remission; and 3) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…Compared with diagnosis, children's BMI z‐score remained significantly higher at the end of the glucocorticoid‐free maintenance phase, which marked the end of treatment and at 5 and 7 years after diagnosis. These findings extend upon previous studies by demonstrating long‐term increases in BMI z‐score, a commonly used and well‐validated measure of adiposity, in children with ALL treated without cranial radiation and with a glucocorticoid‐free maintenance phase.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Compared with diagnosis, children's BMI z‐score remained significantly higher at the end of the glucocorticoid‐free maintenance phase, which marked the end of treatment and at 5 and 7 years after diagnosis. These findings extend upon previous studies by demonstrating long‐term increases in BMI z‐score, a commonly used and well‐validated measure of adiposity, in children with ALL treated without cranial radiation and with a glucocorticoid‐free maintenance phase.…”
Section: Discussionsupporting
confidence: 86%
“…Given these factors and its increased potency for stimulating weight gain, it is plausible that dexamethasone may have a greater obesogenic effect compared with prednisone, as our data would suggest. However, the evidence regarding its long‐term effect on body composition is contradictory . Some studies have found evidence that dexamethasone stimulates greater short‐term increases in standardized measures of BMI than prednisone during and after ALL treatment, as well acute activation of metabolic syndrome components such as insulin resistance, hypertension, and dyslipidemia, while other studies have not …”
Section: Discussionmentioning
confidence: 99%
“…BW loss is a widely reported phenomenon during acute or short‐term glucocorticoid treatment in animals, especially in rodents and at high doses . However, it is worth mentioning that, in humans on long‐term glucocorticoid therapy, BW gain is commonly observed, and this response may be explained by the action of DEX on the BW set‐point, which may be determined by the dose of glucocorticoids and hypothalamic corticotrophin‐releasing hormone concentrations …”
Section: Discussionmentioning
confidence: 99%
“…With an increasing appreciation of the need to start lifestyle interventions early on in therapy for pediatric malignancies, the transtheoretical model may serve as a guide in their development. The well‐established importance of targeting psychosocial variables (SOC and self‐efficacy) during lifestyle counseling highlights the need to enhance our understanding of how psychosocial variables are related to one another and how they may fluctuate throughout the spectrum of cancer care . Inclusion of this knowledge in the design of lifestyle interventions is more likely to lead to sustained behavioral change.…”
Section: Introductionmentioning
confidence: 99%